2022
DOI: 10.1093/molbev/msac028
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Recombination in SARS-CoV-2 Revealed through Genealogical Reconstruction

Abstract: The evolutionary process of genetic recombination has the potential to rapidly change the properties of a viral pathogen, and its presence is a crucial factor to consider in the development of treatments and vaccines. It can also significantly affect the results of phylogenetic analyses and the inference of evolutionary rates. The detection of recombination from samples of sequencing data is a very challenging problem, and is further complicated for SARS-CoV-2 by its relatively slow accumulation of genetic div… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
1
34
0
3
Order By: Relevance
“…Though not yet highly prevalent, evidence for recombination in SARS-CoV-2 has started to appear (VanInsberghe et al ., 2020; Jackson et al ., 2021; Varabyou et al ., 2021; Ignatieva et al ., 2021). As such, it is crucial to know the extent to which recombination is expected to shape SARS-CoV-2 in the coming years, to have methods to identify recombination and to perform phylogenetic reconstruction in the presence of recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Though not yet highly prevalent, evidence for recombination in SARS-CoV-2 has started to appear (VanInsberghe et al ., 2020; Jackson et al ., 2021; Varabyou et al ., 2021; Ignatieva et al ., 2021). As such, it is crucial to know the extent to which recombination is expected to shape SARS-CoV-2 in the coming years, to have methods to identify recombination and to perform phylogenetic reconstruction in the presence of recombination.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Furthermore, genetic recombinations were reported or suspected, based on the concurrent detection in consensus genomes of signature mutations of different mutants or variants. 10,12,[14][15][16][17][18][19][20][21][22][23][24] A study detected up to 1,175 (0.2%) putative recombinant genomes among 537,360 genomes and estimated that up to 5% SARS-CoV-2 having circulated in the USA and UK could be recombinants. 16 Two pandemic variants, Delta and Omicron 21K (Nextclade classification 25,26 )/BA.1 (Pangolin classification 27 ), recently succeeded each other as the predominant viruses but cocirculated for a period of several weeks, creating conditions for co-infections and subsequently recombinations.…”
Section: Text Introductionmentioning
confidence: 99%
“…Co-infections with two variants were reported including recently with SARS-CoV-2 Delta and Omicron variants (Jackson et al, 2021; Francisco et al, 2021; Taghizadeh et al, 2021; Rockett et al, 2022). Furthermore, genetic recombinations were reported or suspected, based on the concurrent detection in consensus genomes of signature mutations of different mutants or variants (Yi, 2020; Yeh and Contreras, 2020; VanInsberghe et al, 2020; Gallaher, 2020; Jackson et al, 2021; Haddad et al, 2021; Makarenkov et al, 2021; Varabyou et al, 2021; Leary et al, 2021; Taghizadeh et al, 2021; Lohrasbi-Nejad, 2022; Kreier, 2022; Ignatieva et al, 2022). A study detected up to 1,175 (0.2%) putative recombinant genomes among 537,360 genomes from the GISAID database and estimated that up to 5% SARS-CoV-2 having circulated in the USA and UK could be recombinants (VanInsberghe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported the detection of SARS-CoV-2 recombinant lineages circulating at a low frequency ( 11 , 12 , 18 21 ). Nevertheless, these studies were restricted to detecting the inter-host dissemination of genomes post-recombination events, which could be biased by spurious mutations generated due to library preparation, laboratory contamination, and unavailability of raw sequenced data.…”
Section: Discussionmentioning
confidence: 99%